Cultural Projects of Samuel Glusberg. Contributions to the history of the independent publishing in the first half of the twentieth century Latin american (Andamios, Revista de Investigación Social, 2015)
Our article examines the immense cultural work that Samuel Glusberg —or Enrique Espinoza, his literary pseudonym— developed in Argentina, between 1919 and 1935, and Chile, between 1935  and 1973. Within this exercise, our inquiry exposes that the characteristics printed in his diverse editorial projects locates him in a particular position of the cultural field of that period, a position   that we could summarize as of resistance against the mercantilist tendencies that were taking place in the cultural space and of a strong political, ideological and a esthetical independency. Also, in an effort of inscribing his initiatives inside the social framework where they belonged, this work constitutes an approximation to the challenges that confronted independent publishing during the first half of the twentieth century.
Keywords: Samuel Glusberg; Enrique Espinoza; independent publishing